Edukasi Bela Negara Bagi Mahasiswa PPG Universitas Cenderawasih Untuk Membangun Karakter Nasionalisme dan Patriotisme - Pistanty, Mingle A; Sarima; Ginting, Inriyatni Sri Pertiwi; Paotonan, Nesliani; Ashari, Makmum; Lintong, Fikstif Donal (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
Teacher Professional Education (PPG) students as prospective educators have an important role in instilling national values in students. However, their understanding of the concept of defending the country still needs to be improved. Therefore, this service activity aims to provide education about defending the country to PPG students of Cenderawasih University in order to build their nationalism and patriotism character. The subjects in this activity are all students of the Cenderawasih University Pre-Service PPG Program. The scheme of community service is by going directly to the students to socialize and provide understanding to PPG students regarding National Defense which is the theme of this community service. There was a significant increase in student understanding after participating in this educational activity. Before being given the material, only 40% of students obtained a score above 70 in the pre-test, while after education, as many as 85% of students achieved this score in the post-test. This increase shows that the methods applied in this activity are effective in increasing students' understanding of defending the country. The national defense education provided to PPG students of Cenderawasih University has been proven to be able to increase their understanding of the importance of nationalism and patriotism. For the next service, it is recommended to have a more interactive approach and a wider range of participants so that the impact is more optimal